A comparative study for biomass gasification in bubbling bed gasifier using Aspen HYSYS - ÖZVEREN, UĞUR (Elsevier Ltd, 2021)
This study presents bubbling bed gasification characteristics of the agricultural and livestock wastes performing sensitivity analysis in the Aspen HYSYS process simulator. Effects of operating conditions on syngas composition, syngas exergy, and syngas lower heating value were examined. Sensitivity analysis results indicated the optimum steam/biomass ratio (0.2–0.3) and gasifier temperature (700 °C–800 °C) to produce syngas with the highest quality. The novelty of the work can be divided into two parts: initially, it is a comparative study for gasification of agricultural and livestock wastes in bubbling bed gasifier and secondly, although fluidized gasifiers have been modeled and comparative studies have been conducted with Aspen Plus® before, there are no similar analyses for bubbling bed gasifiers for agricultural and livestock wastes in Aspen HYSYS, according to our best knowledge. The deductions of this study are significant in terms of development of bubbling bed gasifiers for biomass. © 2020 Elsevier Ltd
Keywords: Aspen HYSYS; Biomass; Bubbling bed gasifier; Gasification; Thermodynamic analysis